Research on the Wind Power Penetration Limit in Power System - Yang Zhang; Hongbo Zhang; Degui Yao; Qiang Li (Institute of Advanced Engineering and Science, 2013)
An approach to calculate the wind farm penetration capacity based on chance constrained programming combining with transient check was presented. A novel model for programming penetration of wind farm under indeterminacy operating mode was presented. Constraint condition consisted of conventional generator output limits, system spinning reserve, transmission lines capability, nodal voltage, system frequency etc, and genetic algorithm based on Monte Carlo simulating was used to solve the problem, and the actual sample system verified the feasibility of the model and method. Results for the application of this approach revealed the influencing factors of penetration of wind farm consisted of the parallel node voltage, the output variation range of wind generating set and mean wind speed etc. The research results have important practical significance, which can guide the actual wind farms in the planning and operation analysis of reality wind farm. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3045